Efficacy of Emergent STA–MCA Bypass for Acute Atherosclerotic ICA Stenosis/Occlusion with Concomitant Chronic Contralateral ICA Occlusion/Stenosis: Two Case Reports - Shimoi, Akihiro; Tsunoda, Sho; Inoue, Tomohiro; Akabane, Atsuya (Asian Journal of Neurosurgery, 2022)
Recombinant tissue-type plasminogen activator with/without endovascular regimen is sometimes not effective for the treatment of acute hemodynamic stroke. Emergent superficial temporal artery-middle cerebral artery (STA–MCA) bypass has been reportedly effective in patients with progressive hemodynamic stroke; however, the effectiveness of urgent STA–MCA bypass for acute internal carotid artery (ICA) stenosis/occlusion with concomitant contralateral chronic ICA stenosis/occlusion, that is considered the worst hemodynamic situations, is unclear. Two cases of acute left ICA stenosis with concomitant right chronic ICA occlusion wherein both developed hemodynamic infarction and were initially treated by maximal medical treatment. Nevertheless, the patients' symptoms had gradually worsened, thus we performed emergency STA–MCA bypass for both cases. Postoperatively, deterioration of imaging and neurological findings was successfully stopped and the patients' condition gradually stabilized. An urgent STA–MCA bypass can be considered as a last resort to prevent progressive neurological deterioration for patients with progressive infarction due to ICA stenosis/occlusion concomitant with contralateral ICA stenosis/occlusion.
Keywords: STA–MCA bypass; progressive stroke; revascularization